Effectivity of Stichopus hermanii Supplementation to Prevent Oral Candidiasis on Rats - Paramita Devi Oktaviani; Endah Wahjuningsih; Dwi Andriani (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2018)
Background: Candida albicans is normal flora of oral cavity that can be pathogenic due to predisposition influence so that trigger Oral candidiasis. Stichopus hermanii suspected as an Oral candidiasis therapy because it contain antioxidant compound, antitumor and antifungi. Objective: Analyzing the effectiveness of Stichopus hermanii supplementation as a protective effect of oral candidiasis in Rats exposure to smoke. Materials and Methods: This experiment is post test only group control design using 35 male rats divided into 5 groups(X). X1 (negative control), X2 (positive control), X3 (Stichopus hermanii powder 0,0225mg/kgBB), X4 (Stichopus hermanii powder 0,045mg/kgBB), X5 (Stichopus hermanii powder 0,09mg/kgBB). Candida albicans induced into the mouth by an oral swab using cotton bud 3 times a week for 8 weeks. Smoke exposure as a predisposition factor be given 3 bars per day for 8 weeks. The rats being killed and tongue biopsies measure the thickness of tongue epithelium. The obtained data analyzation using One Way ANOVA and LSD test. Result: There is a significant difference (p<0.05) between X1 and X2, X1 and X3, X1 and X4, X1 and X5, X2 and X3, X2 and X4, X2 and X5, X3 and X5. Conclusion: Adduction of Stichopus hermanii capable of reducing risk of Oral candidiasis. Supplementation of Stichopus hermanii powder 0,09mg/kgBB is the most effective reduce thickness of the tongue epithelium in the group that exposure to smoke and induced of Candida albicans.